Implementing Good Corporate Governance in Enhancing Village Credit Institutions’ Performance - Ni Putu Natasya Padma Dewi; Sagung Oka Pradnyawati; Putu Kepramareni (Asia Pacific Journal of Management and Education (APJME), 2025)
Village Credit Institutions (Lembaga Perkreditan Desa or LPD) are unique financial organizations found only in Bali, operating under local customary laws. While the number of LPDs continues to grow, their performance and governance quality have not shown similar progress. In 2024, several LPDs were classified as unhealthy, with a notable case in Serangan Village where corruption led to institutional closure. This study explores how Good Corporate Governance (GCG) impacts LPD performance. Using a quantitative approach, data were collected through questionnaires and informal interviews, then analyzed using multiple linear regression. The t-test results indicate that the significance values for each variable are below the 0.05 threshold, indicating that all five GCG principles transparency, accountability, responsibility, independence, and fairness—significantly and positively influence LPD performance. The findings highlight that strong governance practices support ethical operations and performance improvements in local financial institutions. Practically, the study urges LPD management to consistently apply GCG principles to prevent mismanagement and maintain public trust. Local governments and regulators are encouraged to enhance oversight mechanisms rooted in cultural values and offer regular training for LPD leaders